IDENTIFIKASI AKUIFER DENGAN PEMODELAN BAWAH PERMUKAAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DAN DIPOLE-DIPOLE DAERAH PONJONG, GUNUNG KIDUL - Muhammad Dandy Fachrindra; Al Hussein Flowers Rizqi (Retii, 2021)
Gunung Kidul Regency, especially Ponjong District, is known as a barren or dry area, and always suffers from a lack of water to meet domestic needs. The Wonosari area and its surroundings have relatively productive aquifers locally. The purpose of this study was to determine the type, location, depth, thickness, and subsurface 3D modeling using the geoelectric method of Dipole-dipole and Schlumberger configurations. Based on the results of surface data, there are two springs in Grogol Hamlet which are interpreted as appearing because there are cracks in the subsurface rocks and springs in Sumberejo Hamlet which are interpreted as their appearance due to the controlling factor of the Sumberejo Sinistral Fault. Meanwhile, geoelectric data analysis shows the presence of rock layers as a confined aquifer in Garon Hamlet at a depth of 63-87 meters and in Dusun Sumberejo at a depth of 55-68 meters. Key words: aquifer, dipole-dipole, geoelectric, Ponjong, schlumberger.